The status of the Dactylorhiza incarnata populations in the Kalba Altai, Kazakhstan - Alevtina Danilova; Aidar Sumbembayev (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Danilova AN, Sumbembayev AA. 2021. The status of the Dactylorhiza incarnata populations in the Kalba Altai, Kazakhstan. Biodiversitas 22: 3180-3195. The article provides a botanical description of the current state of populations of threatened species Dactylorhiza incarnata (L.) Soo in the Kalba. The ecological analysis of the flora, the ecological optimum of the species, the vitality of plant communities, and the degree of anthropogenic load are presented in the research. On the basis of field surveys, four main populations were identified in 13 typical plant communities. Flora of plant communities of D. incarnata on the Kalba Ridge includes 117 species belonging to 30 families and 80 genera. The ecological optimum of D. incarnata can be spotted on the southeastern slopes with diffused lighting and moderate wind impact. The plant communities with optimal conditions are Filipendulo-Sanguisorbo-Thalictrosum and Carexoto-Equiseto-Filipendulo-Festucosum characterized by highly humid meadows and forest edges with low density and competition. Self-maintenance and reproduction of the species are fulfilled mainly by seeds, less often by vegetative reproduction of the finger root. Due to analysis of the age composition of populations and the dynamics and stability of plant communities the recovery index is within the optimum. Typical indicator species are Thalictrum simplex L., Salix viminalis L., Filipendula ulmaria (L.) Maxim., Sanguisorba officinalis L., Geranium pratense L., Festuca pratensis Huds.